2004
DOI: 10.1111/j.0022-202x.2004.22620.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A Radiation-Induced Immediate Iron Release Is a Key Modulator of the Activation of NF-κB in Human Skin Fibroblasts

Abstract: Ultraviolet A (UVA, 320-400 nm) radiation, an oxidizing component of sunlight, leads to an immediate increase in the labile iron in human skin fibroblasts. Exposure of skin fibroblasts to UVA radiation is also known to induce nuclear factor-kappaB (NF-kappaB) DNA-binding activity, although the underlying mechanism is unclear. We report here that in skin fibroblasts, the extent of NF-kappaB activation by UVA tightly correlates with the level of "UVA-induced" labile iron release as shown by both iron chelation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 68 publications
1
53
0
3
Order By: Relevance
“…In fact, since it has been shown that exposure of skin cells to e.g. UVA induces an immediate release of labile iron [33], this mechanism could be (at least in part) responsible of the inflammatory and oxidative damages reported here. Therefore the photoprotective effects elicited by polyphenolic phytochemicals could involve, as previously suggested, potential iron chelating effects (see e.g.…”
Section: Effect Of Stilbenes On Acute Uvb Radiation-induced Skin Damagesmentioning
confidence: 72%
“…In fact, since it has been shown that exposure of skin cells to e.g. UVA induces an immediate release of labile iron [33], this mechanism could be (at least in part) responsible of the inflammatory and oxidative damages reported here. Therefore the photoprotective effects elicited by polyphenolic phytochemicals could involve, as previously suggested, potential iron chelating effects (see e.g.…”
Section: Effect Of Stilbenes On Acute Uvb Radiation-induced Skin Damagesmentioning
confidence: 72%
“…Firstly, heme oxygenase 1, as the strongest UVA/oxPL regulated gene is essential to restore the cellular heme/iron homeostasis after UVA insult [76,77] and has well established anti-inflammatory properties, including reduction of TNFα synthesis. Glutathione peroxidase and the enzymes necessary for de-novo glutathione synthesis, GCLM and GCLC all contribute to limit UVA induced lipid hydroperoxide generation, which promotes expression of MMP1 (and of its mouse homolog MMP13).…”
Section: Protective Effects Of Pufa / Via Nrf2mentioning
confidence: 99%
“…27 Recently, Reelfs et al have shown that labile iron in skin fibroblast, which is involved in the activation of a number of transcription factors, was released by UVA irradiation. 28 It is also known that 1 O 2 can initiate c-jun N-terminal kinase signaling, which leads to interstitial collagenase induction as well as the synthesis of proinflammatory cytokines in UVA-irradiated fibroblasts. 27 It was also proven that aging skin fibroblasts have decreased catalase activity.…”
Section: Resultsmentioning
confidence: 99%